Game Pembelajaran Interaktif Pengenalan Huruf dan Angka Menggunakan Metode Addie Untuk Anak Usia Dini Berbasis Android - Nugraha, Ahmad Danny; Laila, Siti Nur; Azima, Muhammad Fauzan (Journal of Comprehensive Science, 2025)
Technological developments provide opportunities in creating interactive learning media, especially for early childhood who need an interesting educational approach and in accordance with their developmental stage. The problem raised in this study is the lack of digital-based learning media that is able to optimally attract children's interest in learning. This research aims to design and build Android-based interactive learning media and games using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) method. The results of the study show that the learning media developed is able to significantly increase early childhood learning interest, shown through the results of trials and evaluations involving users and material experts who provide positive responses to aspects of appearance, interactivity, and material suitability. Thus, this application is expected to be an innovative and fun alternative to learning media.